2021
DOI: 10.1039/d1bm01184g
|View full text |Cite
|
Sign up to set email alerts
|

Bioenzyme-responsivel-arginine-based carbon dots: the replenishment of nitric oxide for nonpharmaceutical therapy

Abstract: Nitric oxide (NO) is a short-lived, bioactive gas which has been affinitive to cardiovascular diseases as well as cancer biology, and the deficiency of NO may cause serious pathological responses....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In addition, the antitumor effect observed in the AM­(B)­LD+NIR group, where PTT was combined with NO under NIR irradiation, was significantly superior to that in the AM­(B)­LD group ( p < 0.001). There are various pathways that stimulate NO production, such as pH, enzymes, and NIR . However, in contrast to the currently reported NO therapy literature, , our system uniquely combined the dual functionalities of inducing NO production under NIR irradiation and serving as an initiator for PTT.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the antitumor effect observed in the AM­(B)­LD+NIR group, where PTT was combined with NO under NIR irradiation, was significantly superior to that in the AM­(B)­LD group ( p < 0.001). There are various pathways that stimulate NO production, such as pH, enzymes, and NIR . However, in contrast to the currently reported NO therapy literature, , our system uniquely combined the dual functionalities of inducing NO production under NIR irradiation and serving as an initiator for PTT.…”
Section: Resultsmentioning
confidence: 99%
“…l -Citrulline has minimal deleterious effects on the human body, making l -Arg a perfect NO donor medication. Recent research indicates that l -Arg, for the purpose of donor-mediated NO release, has a positive therapeutic impact in the treatment of cervical cancer, breast cancer, glioma, and other malignancies without causing side effects . By creating a nanoplatform that produces oxidative photogenerated holes in reaction to light, Xiao and co-workers oxidize arginine residues to create NO when 660 nm laser light is applied.…”
Section: Small Molecular Weight No Donorsmentioning
confidence: 99%
“…Recent research indicates that L-Arg, for the purpose of donormediated NO release, has a positive therapeutic impact in the treatment of cervical cancer, breast cancer, glioma, and other malignancies without causing side effects. 57 By creating a nanoplatform that produces oxidative photogenerated holes in reaction to light, Xiao and co-workers oxidize arginine residues to create NO when 660 nm laser light is applied. The in vitro and in vivo findings indicated that poly-L-arginine-modified carbon-dots-doped graphitic carbon nitride nanomaterial ArgCCN has the capacity to produce NO effectively in both positive and hypoic settings and to trigger apoptosis in tumor cells when exposed to laser light.…”
Section: N-diazeniumdiolatesmentioning
confidence: 99%
“… 25 , 26 Among them, L-arginine (L-Arg), as a substrate for inducible nitric oxide synthases (iNOS), is a promising NO donor in response to endogenous hydrogen peroxide (H 2 O 2 ) to produce NO. 27 , 28 However, the application of L-Arg is compromised by its poor cellular internalization and nontargeted biodistribution. Furthermore, similar to ROS, NO and RNS are very reactive and have difficulty reaching the mitochondria.…”
Section: Introductionmentioning
confidence: 99%